Youth Unemployment in Advanced Europe : Okun's Law and Beyond - Banerji, Angana; Lin, Huidan; Saksonovs, Sergejs (Washington, D.C. : International Monetary Fund, 2015)
The crisis has intensified what was previously a chronic unemployment problem in Europe; youth unemployment is now at unprecedented highs in some European countries. This paper assesses the main drivers of youth unemployment in Europe. It finds that much of the increase in youth unemployment rates during the crisis can be explained by output dynamics and the greater sensitivity of youth unemployment to economic activity than adult unemployment. Labor market institutions also play a significant role in explaining the persistently high levels of youth unemployment, especially the tax wedge, minimum wages relative to the median wage, spending on active labor market policies, the opportunity cost of working (measured by the unemployment benefits), vocational training, and labor market duality. This suggests that policies to address youth unemployment should be comprehensive and country-specific, focused on reviving growth and advancing labor market reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet